Hox function and specificity: a tissue centric view - Pinto, Pedro; Domsch, Katrin; Lohmann, Ingrid (Seminars in cell & developmental biology, 2024)
Since their discovery, the Hox genes, with their incredible power to reprogram the identity of complete body regions, a phenomenon called homeosis, have captured the fascination of many biologists. Recent research has provided new insights into the function of Hox proteins in different germ layers and the mechanisms they employ to control tissue morphogenesis. We focus in this review on the ectoderm and mesoderm to highlight new findings and discuss them with regards to established concepts of Hox target gene regulation. Furthermore, we highlight the molecular mechanisms involved the transcriptional repression of specific groups of Hox target genes, and summarize the role of Hox mediated gene silencing in tissue development. Finally, we reflect on recent findings identifying a large number of tissue-specific Hox interactor partners, which open up new avenues and directions towards a better understanding of Hox function and specificity in different tissues.
Online verfügbar am 12. Dezember 2022, Artikelversion vom 3. August 2023
Gesehen am 28.11.2023